Edukasi dan Demonstrasi Kesehatan Berbasis Masyarakat untuk Peningkatan Kualitas Hidup - Susanti, Rahmi; Adrianto, Ratno; Nada, Abira Ivanca Audya; Huwaidah, Ayu; Hutauruk, Hutauruk; Jumliana, Jumliana; Ulfah, Meilida; Rangga, M.; Auralia, Syalmitha; Khusnul, Vika (UPT Penerbitan Universitas Jember, 2023)
The focus group discussion results and a survey involving 100 heads of households revealed that 62% consume fast food, 34% have a history of degenerative diseases, 31% manage waste by burning it, 49% smoke inside the house, and 64% complain of respiratory diseases. The health issues observed are interconnected, such as the high sodium content in fast food consumption which can lead to degenerative disease symptoms. The aim of this community service is to empower and intervene in the community, thereby enhancing knowledge and fostering an attitude to change inappropriate health behaviours. The implementation method involves lectures with demonstrations, the use of video media, and special exercises for degenerative diseases. Partners involved include the local community leader, P2KB, and eleven (11) academics. Summative evaluation is conducted on the target community involved in activities like pre-post tests. The results achieved from the program implementation are that 86.67% experienced an increase in knowledge about healthy food, 98.18% of the targets received information about the dangers of smoking inside the house, and 95.56% experienced an increase in knowledge related to degenerative diseases.Keywords: fill my plate, hypertension exercise, cigarette smoke demonstration, community empowerment.